EFFECT OF 6 WEEKS OF ROPE TRAINING ON THE DELICATE SKILLS OF ELEMENTARY SCHOOL GIRL STUDENTS - KHANJANI, MINA; GRIVEDEHI, MOJTABA BRARARZADE; FORGHANI OZRUDI, MOHAMMADBAGHER (Innovare Journal of Social Sciences, 2023)
The object of this research is to determine the effect of 6 weeks of rope training on the delicate skills of elementary school girl students. The study has been done in semi experimental method. Statistical society includes all girl students in fourth grade in which are learning Tanavarz National Project and are education in 121 schools in Babul city. Statistical sample has been selected randomly and in first Stage 3 schools and then in any school 1 class and in any class, about 15 students have been selected. They have been divided in three groups of control (n=15), speedy (n=15), and demonstrations (n=15) equally. Statistical datum has been analyzed through one-sided variance, non-parametric test of Kruskal–Wallis, and post hoc test of Tukey by SPSS 22 software in meaningful level of p≤0.05. Datum result showed that participants do have the mean height of 1.37±0.07 m and weight of 33.4±9.6 kg. Findings showed rope training project from statistical view in the two groups of showing and speedy does have meaningful influence on speed and agility of upper part of body and grow of fine motor skills than control group. However, its influence on the growth of response speed and motor visual control was not meaningful in three groups. In other hand, there is no meaningful difference among speed grow and agility of upper part of body and fine motor skills in speedy-demonstrations group (p>0.05), and only there is meaningful difference among the mean growth of speed and agility of upper part of body and fine motor skill in speedy-control group and demonstrations-control group (p<0.05). Finally, the result shows rope training project could be feasible program for the growth of girl’s fine motor skill.